The efficiency of insulin production and its content in insulin-expressing model β-cells correlate with their Zn2+ levels - Dzianová, Petra; Asai, Seiya; Chrudinová, Martina; Kosinová, Lucie; Potalitsyn, Pavlo; Šácha, Pavel; Hadravová, Romana; Selicharová, Irena; Kříž, Jan; Turkenburg, Johan P; Brzozowski, Andrzej Marek; Jiráček, Jiří; et al. (Open biology, 2020)
Insulin is produced and stored inside the pancreatic β-cell secretory granules, where it is assumed to form Zn2+-stabilized oligomers. However, the actual storage forms of this hormone and the impact of zinc ions on insulin production in vivo are not known. Our initial X-ray fluorescence experiment on granules from native Langerhans islets and insulinoma-derived INS-1E cells revealed a considerable difference in the zinc content. This led our further investigation to evaluate the impact of the intra-granular Zn2+ levels on the production and storage of insulin in different model β-cells. Here, we systematically compared zinc and insulin contents in the permanent INS-1E and BRIN-BD11 β-cells and in the native rat pancreatic islets by flow cytometry, confocal microscopy, immunoblotting, specific messenger RNA (mRNA) and total insulin analysis. These studies revealed an impaired insulin production in the permanent β-cell lines with the diminished intracellular zinc content. The drop in insulin and Zn2+ levels was paralleled by a lower expression of ZnT8 zinc transporter mRNA and hampered proinsulin processing/folding in both permanent cell lines. To summarize, we showed that the disruption of zinc homeostasis in the model β-cells correlated with their impaired insulin and ZnT8 production. This indicates a need for in-depth fundamental research about the role of zinc in insulin production and storage.
Keywords: cytoplazmatická granula; Insulin; exprese genu; chemická frakcionace; Gene Expression; RNA, Messenger; Glucose; Male; inzulin; Cytoplasmic Granules; zinkový transportér 8; glukosa; mužské pohlaví; Flow Cytometry; Langerhansovy ostrůvky; krysa rodu Rattus; průtoková cytometrie; Animals; zvířata; beta-buňky; Rats; Zinc Transporter 8; Chemical Fractionation; zinek; Insulin-Secreting Cells; Islets of Langerhans; Zinc; messenger RNA